Algorithmic Portfolio Optimization for Retail Investors: Robo-Advisor Performance - Rathod, Hasmukh Devidas (Journal of Research in Science and Engineering, 2025)
This article explores the potential of Robo Advisors to revolutionize capital market investing for small investors. It discusses how technological advancements in financial services can offer cost efficient, accessible, and personalized investment strategies that are traditionally available only to high net worth individuals. The article examines the benefits of Robo Advisors, including lower fees, diversification, and ease of access, and argues for their growing importance in democratizing investment opportunities.